Preparation method of carbon fiber screen supporting structure
By graphitizing, oxidizing and electrolyzing the carbon fiber, adding aminocarbon nanotubes for orthogonal laying and hot-pressing forming, combined with electric spark wire cutting, the carbon fiber screen support structure in the prior art is solved inadequate rigidity and poor thermal conductivity of the carbon fiber screen support structure in the prior art. The problem of this is to realize a carbon fiber screen support structure with high thermal conductivity and high modulus, which improves the mobile phone's user experience and heat dissipation effect.
Patent Information
- Application Number
- CN202411515864.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing carbon fiber screen support structure is insufficient rigidity and poor thermal conductivity in folding screen mobile phones, making it difficult to meet the requirements of lightweight and high-precision processing. It is easy to have edge wear, fiber pulling, material layering and other problems during the processing process, which affects the appearance and performance. .
After continuous PAN-based carbon fiber and asphalt-based carbon fibers are graphitized, oxidized and electrolyzed, amino-aminolated carbon nanotubes are added, and orthogonal laying and hot-pressing are carried out in the epoxy resin film, combined with electric spark wire cutting Processing to form a carbon fiber screen support structure with high thermal conductivity and high modulus.
It realizes a carbon fiber screen support structure with high thermal conductivity and high modulus, simplifies processing technology, improves appearance yield and accuracy, reduces water ripple generation, and improves the heat dissipation effect of the mobile phone.
Smart Images

Figure CN119241874A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon fiber product, and in particular to a method for preparing a high thermal conductivity carbon fiber screen support structure. Background Art
[0002] In foldable phones, the screen support layer is a critical component that needs to withstand various stresses in daily use while remaining lightweight. It also needs to have a certain degree of rigidity to ensure that the screen does not deform when pressed and does not produce defects such as water ripples. Currently, metal sheet substrates have poor bending effects and poor durability. They have creases after long-term use, which can easily damage the phone screen and shorten its service life. They are also inconvenient to process and have a low yield rate for processed products.
[0003] Carbon fiber materials are applied to the back of the flexible screen to support and protect the entire flexible screen, making the flat area rigid and reducing screen creases. The total thickness of the existing carbon fiber screen support layer is about 0.15mm. When the thickness is thicker, it is difficult to meet the market's requirements for the thinness of folding screen mobile phones. When the thickness is thinner, the rigidity is insufficient and it is difficult to meet the screen support effect. The conventional processing methods of carbon fiber composite materials are tool cutting and cutting machine processing. During the processing, problems such as severe edge wear, fiber pulling, and material delamination are prone to occur, which is difficult to meet the requirements of the consumer electronics field for appearance quality, high precision, and high yield. At the same time, carbon fiber composite materials have poor thermal conductivity. The temperature of the mobile phone rises during use, which will not only reduce the performance of the mobile phone, but also affect the user experience. To this end, it is necessary to find a screen support structure that is lightweight, high-modulus, and has a certain heat dissipation effect. Moreover, in order to ensure the display effect and performance of the folding screen mobile phone, the use of a high-rigidity and high-thermal conductivity support plate under the substrate is the key to ensuring the user experience of the folding screen. Therefore, providing a support structure with a simple preparation method, light and thin, and high modulus to ensure that it has strong rigidity and a certain thermal conductivity is already one of the problems that need to be solved in this field.
[0004] In the prior art, the invention patent application with publication number CN114311872A discloses a carbon fiber screen support structure suitable for a folding screen, wherein the carbon fiber screen support structure of the folding screen comprises: a first direction carbon fiber layer; a second direction carbon fiber layer; each first carbon fiber in the first direction carbon fiber layer is arranged at intervals along the first direction, and each second carbon fiber in the second direction carbon fiber layer is arranged at intervals along the second direction, and the first direction is arranged perpendicular to the second direction; the first direction is the X-axis direction, the second direction is the Y-axis direction, the folding axis of the folding screen is arranged parallel to the Y-axis, and the central area of the first direction fiber layer along the X-axis direction is a hollow area, and only the second direction carbon fiber layer is arranged in the hollow area. Only the second direction carbon fiber layer is laid in the hollow area of the carbon fiber screen support structure, and this processing method is not easy to process into mass production, and the hollow area is composed of fibers in a single direction, so the strength is relatively small, the service life is short, and the scope of use is limited.
[0005] In the prior art, the utility model patent application with publication number CN 217238995 U discloses a flexible folding screen carbon fiber support plate, including a carbon fiber composite layer, the carbon fiber composite layer is composited by N layers of carbon fiber prepreg layers, N is an odd number greater than 2, the carbon fiber prepreg layers are stacked and laid, and then fused into one by vacuuming, heating and pressurizing, the carbon fiber composite layer is cut to the corresponding specifications according to the specifications of the flexible folding screen, and mesh through holes are opened in the area of the carbon fiber composite layer corresponding to the folding and winding after cutting. The mesh through holes are formed by laser cutting or etching or CNC milling, which easily produces traces of burning or corrosion on the edge of the carbon fiber plate, affecting the appearance and performance.
[0006] In the prior art, the invention patent application with publication number CN 114536810 A discloses a carbon fiber support plate and its preparation method and application, wherein the preparation method comprises the following steps: (1) pre-treating a hot pressing mold; (2) laying a carbon fiber prepreg on the pre-treated hot pressing mold obtained in step (1), and then sequentially performing vacuum treatment, curing and molding treatment, and demolding to obtain a carbon fiber support plate blank; (3) attaching a heat shrink film to the surface of the carbon fiber support plate blank obtained in step (2), and then performing laser treatment to obtain the carbon fiber support plate. Since the laser will generate local high temperature during the cutting process, it will cause material deformation and affect the processing accuracy. In addition, the high temperature generated by laser processing will accelerate the oxidation of the material, affecting subsequent processing and use. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a lightweight carbon fiber screen support structure with high thermal conductivity and high modulus. The technical solution adopted by the present invention is as follows:
[0008] A method for preparing a carbon fiber screen support structure comprises the following steps:
[0009] S1: After graphitizing continuous PAN-based carbon fibers and continuous asphalt-based carbon fibers, oxidizing the PAN-based carbon fibers and the asphalt-based carbon fibers, electrolyzing, washing, drying, sizing, and baking, surface-modified PAN-based carbon fibers and surface-modified asphalt-based carbon fibers are obtained;
[0010] S2: impregnating the surface-modified PAN-based carbon fiber and the surface-modified asphalt-based carbon fiber on the surface of the epoxy resin film loaded with amino carbon nanotubes, and connecting the surface-modified PAN-based carbon fiber and the surface-modified asphalt-based carbon fiber to an electric field during the impregnation process, so that the carbon nanotubes are vertically rooted on the surface of the carbon fiber to obtain the surface-modified PAN-based carbon fiber prepreg and the surface-modified asphalt-based carbon fiber prepreg;
[0011] S3: alternately orthogonally laying two layers of surface-modified PAN-based carbon fiber prepreg and one layer of surface-modified asphalt-based carbon fiber prepreg, so that a layer of surface-modified asphalt-based carbon fiber prepreg is sandwiched between the two layers of surface-modified PAN-based carbon fiber prepreg, and then orthogonally laying and hot pressing to obtain a rough blank of a carbon fiber support structure; or
[0012] Three layers of surface-modified asphalt-based carbon fiber prepreg are continuously orthogonally laid and then hot-pressed to obtain a rough blank of a carbon fiber support structure; finally, the rough blank is subjected to electric spark wire cutting to obtain a carbon fiber screen support structure.
[0013] The oxidation comprises the steps of ultrasonic wave-hydrogen peroxide combined oxidation treatment;
[0014] The concentration of hydrogen peroxide used in the ultrasonic-hydrogen peroxide combined oxidation treatment is 5wt%;
[0015] The ultrasonic-hydrogen peroxide combined oxidation treatment adopts an ultrasonic frequency of 20-25kHz;
[0016] The ultrasonic power used in the ultrasonic-hydrogen peroxide combined oxidation treatment is 800-1500W;
[0017] The ultrasonic wave-hydrogen peroxide combined oxidation treatment is carried out for 100-120 seconds.
[0018] The electrolyte used in the electrolysis is (NH 4 ) 3 PO 4 NH 4 HCO 3 NH 4 ) 2 SO 4 or NH 4 H 2PO 4 One of the solutions;
[0019] The mass fraction used in the electrolysis is 2-2.5wt%;
[0020] The current used in the electrolysis is 0.5-1.5A;
[0021] The electrolysis time is 30-60s.
[0022] The length of the amino carbon nanotubes is 5 to 15 μm, and the diameter is 8 to 20 nm;
[0023] The surface density of the carbon nanotubes on the surface of the resin film is 0.07 to 0.22 g / m 2 .
[0024] The loading process includes dispersing the amino carbon nanotubes in an active diluent at a mass ratio of 5wt%, dispersing them by ultrasonication for 2h at a power of 800-1000W, and then concentrating them in vacuum at 80°C to a volume of 1 / 4 of the original volume to obtain a carbon nanotube dispersion, and then spraying the liquid carbon nanotube dispersion onto the surface of the epoxy resin film.
[0025] The active diluent is one of benzyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether and allyl glycidyl ether.
[0026] The power-on step includes connecting the carbon fiber to a negative electrode of -24 to -36V and connecting the cold plate of the prepreg machine to a positive electrode of 12V. When the orthogonal laying is performed, the surface density of the surface-modified PAN-based carbon fiber prepreg is 20 to 30 g / m 2 , fiber surface density is 10g / m 2 ~21g / m 2 , the resin content is 20-40wt%, and the thickness is 12μm-30μm;
[0027] When orthogonally laid, the surface density of the surface-modified asphalt-based carbon fiber prepreg is 110 to 145 g / m 2 , fiber surface density 75~100g / m 2 , the resin content is 25-30wt%, and the prepreg thickness is 60-80μm;
[0028] The tensile modulus of the asphalt-based carbon fiber layer is greater than 700-850 GPa, and the thermal conductivity is 350-550 W / m·K.
[0029] The method for preparing the carbon fiber branch structure further includes a processing step;
[0030] The machining includes the steps of using wire electric discharge machining;
[0031] The power supply voltage used in the EDM wire cutting process is 80V, the servo reference voltage is 8-12V, the servo feed speed is 1.5-2.5mm / min; the peak current is 6.4-8.0A, the pulse width interval is 18-22μs, and the pulse width is 0.15μs-0.3μs;
[0032] The electrode wire used in the electric spark wire cutting process is a negative polarity electrode wire;
[0033] The electrode wire and interelectrode medium are deionized water.
[0034] The overall thickness of the carbon fiber screen support structure is 85 μm to 140 μm.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The preparation method of the high thermal conductivity carbon fiber screen support structure provided by the present invention has a simple process, good appearance, high processing precision, and is conducive to industrial production; the carbon fiber screen support structure has high rigidity, can achieve better support effect under the premise of being lighter and thinner, and reduce the generation of water ripples; at the same time, it has excellent heat conduction ability, which improves the heat dissipation effect during the use of the mobile phone. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the preparation of the adhesive film containing carbon nanotubes;
[0038] Figure 2 Schematic diagram of high thermal conductivity carbon fiber prepreg impregnation composite;
[0039] Figure 3 This is a schematic diagram of carbon fiber prepreg hot press molding layup;
[0040] Figure 4 Schematic diagram of the distribution of carbon nanotubes inside the prepreg material. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0042] The present invention provides a method for preparing a carbon fiber branch structure. Specifically, the method comprises the following steps:
[0043] First, the continuous carbon fiber is unwound by pulling, and then the carbon fiber is graphitized, and then the carbon fiber is surface modified by ultrasonic-hydrogen peroxide to oxidize its surface, and then the carbon fiber is electrolyzed, washed, dried, sizing, baked and wound to obtain continuous carbon fiber with carboxylated surface; the above carbon fiber is PAN-based carbon fiber and continuous asphalt-based carbon fiber.
[0044] Then, a hot melt prepreg is prepared by a two-step hot melt method. Specifically, in the first step, the amino carbon nanotube dispersion is evenly sprayed on the surface of the resin film during the film preparation. In the second step, the carbon nanotubes are vertically rooted on the carbon fiber surface by applying an electric field and chemical crosslinking during the impregnation process. The specific schematic diagram is shown in FIG. Figure 1 and Figure 2 As shown. After the carbon fiber is electrified, due to electrostatic induction, the amino carbon nanotubes with positive charges on the surface gradually migrate to the cathode and are vertically rooted on the surface of the carbon fiber, and are radially embedded on the surface of the carbon fiber. Since CNTs have extremely strong dielectric properties, polarization will occur under external electric field conditions. The polarized CNTs can be regarded as electric dipoles. The electric field force acting on the positive and negative charges forms a force couple. The electronic structure in CNTs shows obvious anisotropy. The dipole parallel to the axis is much larger than the dipole perpendicular to the axis. Under the action of the external electric field, the CNTs with high polarizability produce directional twisting in the direction of the electric field, so that the carbon nanotubes are directional and orderly arranged parallel to the direction of the electric field. At the same time, the non-uniform electric field near the tip of the CNTs causes the induced dipole to move toward the area with high field strength (carbon fiber).
[0045] Then, hot pressing is performed. Specifically, the carbon fiber prepreg is orthogonally laid on a pre-treated smooth hot pressing mold, and a stainless steel precision gasket is used next to the prepreg to control the hot pressing thickness. Then, vacuum treatment, curing and molding treatment, demoulding and machining treatment are performed in sequence to obtain a carbon fiber screen support structure.
[0046] Specifically, the orthogonal laying is to lay three layers of continuous PAN-based carbon fiber and continuous asphalt-based carbon fiber prepreg orthogonally, wherein the first and third layers are orthogonally laid with continuous PAN-based carbon fiber prepreg or asphalt-based carbon fiber prepreg; the second layer is laid with asphalt-based carbon fiber prepreg. Asphalt-based carbon fiber is relatively brittle, and the use of asphalt-based carbon fiber in the middle can reduce the damage to the mechanical properties of the composite material during processing, so that the fiber performance can be fully exerted; in addition, PAN-based carbon fiber can be made thinner, usually the minimum can be 12μm to 30μm, so that the support layer can be made thinner more easily.
[0047] Finally, the carbon fiber screen support structure is cut and surface processed to be applied to support the screen.
[0048] Preferably, the graphitization temperature of the continuous carbon fiber is 2600-2900°C;
[0049] Preferably, the surface modification process uses 5% ultrasonic-hydrogen peroxide combined oxidation treatment, the ultrasonic frequency is 20-25kHz, the ultrasonic power is 800-1500W, the length of the electrolytic cell and the fiber winding speed are controlled to ensure that the fiber is in the hydrogen peroxide solution for 120s; preferably, the electrolyte in the electrolysis process is 2.5wt% (NH 4 ) 3 PO 4 NH 4 HCO 3 NH 4 ) 2 SO 4 and NH 4 H 2 PO 4 One of the solutions, the current passing through the carbon fiber is fixed at 1A, the fiber winding speed is controlled, and the fiber treatment time in the electrolytic cell is 60s;
[0050] The treated carbon fiber enters the water washing device and is washed in deionized water to remove water-soluble impurities on the fiber surface;
[0051] Preferably, the carbon nanotubes are amine-modified multi-walled carbon nanotubes, with a length of 5 to 15 μm and a diameter of 8 to 20 nm; preferably, the length of the amino-modified carbon nanotubes is 5 to 15 μm. When used, the carbon nanotubes are dispersed in an active diluent at a mass ratio of 5 wt%, and are dispersed by ultrasonication for 2 h at a power of 800 to 1000 W, and then the dispersion is placed in a vacuum oven at 80°C to evaporate to 1 / 4 of the original volume, to obtain a liquid carbon nanotube dispersion;
[0052] Furthermore, the active diluent is one of benzyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether;
[0053] Preferably, the carbon nanotube dispersion is sprayed onto the film surface at high pressure, and the surface density of the carbon nanotubes is ensured to be 0.07-0.22 g / m by controlling the spraying speed and the film production speed. 2 Other methods such as electrospraying, CNTs dispersion spraying molding based on ion thermal excitation, etc. are also within the scope of the claims of the present invention; the amine functional groups on the surface of liquid amino carbon nanotubes can undergo a ring-opening reaction with epoxy groups, thereby participating in a cross-linking reaction and forming a flexible interface layer on the surface, slowing down the aggregation trend of carbon nanotubes caused by the increase in carbon tube content; liquid carbon nanotube reinforcement can effectively solve the technical problems of increased resin viscosity, reduced dispersibility and poor processability after the addition of nanoparticles.
[0054] Preferably, during the impregnation process, the carbon fiber is connected to a negative electrode of -24 to -36V. The negative electrode can be added to the filament comb or to a separate guide roller electrode. Before the prepreg machine cold plate, the prepreg machine cold plate is connected to a 12V positive electrode. The carbon fibers repel each other due to electrostatic effects and are evenly distributed in the film; during the impregnation process, the viscosity of the resin decreases due to heat, the carbon nanotubes migrate under the pressure of the hot pressing rollers and spontaneously arrange themselves due to the electric field, the ultrasonic rod increases the free movement of the carbon nanotubes, and due to electrostatic induction, the amino carbon nanotubes with positive charges on the surface gradually migrate to the cathode and are vertically rooted on the carbon fiber surface, and are radially embedded on the carbon fiber surface.
[0055] Preferably, tempered glass and stainless steel plates are used as hot pressing molds. The material of the hot pressing mold can also be mold aluminum and a combination thereof. Before using the mold for the first time, it is necessary to use isopropyl alcohol or acetone to remove oil stains in the mold. Before each subsequent use of the mold, it is necessary to clean it with a mold cleaning agent, apply a mold release agent 3 to 5 times, wipe it with a dry cloth after applying the mold release agent, and then apply the mold release agent. After all the coating is completed, let it stand for 5 to 10 minutes.
[0056] Preferably, the carbon fiber prepreg is orthogonally laid in three layers, the first and third layers are PAN-based carbon fiber layers or high-performance asphalt-based carbon fiber layers, and the prepreg surface density of the carbon fiber layer is 20-30 g / m 2 , fiber surface density 10g / m 2 ~21g / m 2 , the resin content is 20-40wt%, the prepreg thickness is 12μm-30μm; the second layer is a high-performance asphalt-based carbon fiber layer, the carbon fiber tensile modulus is greater than 750GPa, the thermal conductivity is 350-550W / m·K, and the prepreg surface density is 110-145g / m 2 , resin content is 25-30wt%, fiber surface density is 75-100g / m 2 , the prepreg thickness is 60~80μm;
[0057] Specifically, the stainless steel precision gasket is laid on the mold, around the prepreg, and the stainless steel precision gasket can be used as one piece, or two or three pieces are stacked. The thickness of the stainless steel precision gasket or the total thickness of the stainless steel precision gasket after stacking is consistent with the total thickness of the prepreg, and the thickness tolerance of the stainless steel precision gasket is less than ±5μm;
[0058] Optionally, a matte film can be laid between the prepreg and the mold to control the surface texture of the carbon fiber screen support structure of the folding screen. The size of the matte film needs to cover the stainless steel precision gasket area;
[0059] Preferably, one stainless steel precision gasket is used, and the stainless steel precision gasket is spaced 10 to 15 mm from the prepreg;
[0060] Preferably, a stainless steel plate is used on the upper side of the prepreg, and a tempered glass is used on the lower side as a hot pressing mold, so as to ensure that the temperature of the prepreg on the upper side is slightly higher than that on the lower side to facilitate the discharge of pores, and at the same time ensure that the upper and lower prepregs have different shrinkage rates after cooling to facilitate demoulding;
[0061] Preferably, the negative pressure of the vacuum treatment is -0.1 to -0.12 MPa, and the molding is carried out by using an autoclave, and the autoclave uses air as the medium, and the air pressure is 0.6 to 1.2 MPa;
[0062] During curing, a two-step temperature increase is used to carry out the epoxy system chain extension cross-linking reaction and curing reaction, that is, first the temperature is increased to 80-95 degrees Celsius, kept warm for 30 minutes, then the temperature is increased to 120-135 degrees Celsius, kept warm for 2 hours, and then cooled to below 60 degrees Celsius before taking out the rough carbon fiber screen support structure.
[0063] Preferably, the wire-cutting electrospark machining method is used, the power supply voltage is 80V, the servo reference voltage is 8-12V, the peak current is 6.4-8.0A, the electrode wire is negative polarity, the pulse width interval is 18-22μs, the pulse width is 0.15μs-0.3μs, the inter-electrode medium is deionized water, and the servo feed speed is 1.5-2.5mm / min;
[0064] According to the product design requirements, after the machining is completed, the support layer is sandblasted and coated to obtain the carbon fiber screen support structure product of the folding screen. The overall thickness of the carbon fiber screen support structure is preferably 85μm to 140μm.
[0065] The present invention is further described below in conjunction with specific embodiments.
[0066] Example 1
[0067] This embodiment provides a high thermal conductivity carbon fiber screen support layer, and the preparation method of the high thermal conductivity carbon fiber screen support layer includes the following steps:
[0068] Polyacrylonitrile-based carbon fiber and asphalt-based carbon fiber were treated separately. Specifically, after the continuous carbon fiber was unrolled, it was graphitized at 2900°C, and then surface modified, electrolyzed, washed, dried, dried, sizing, dried and wound to obtain two continuous amino-functionalized carbon fibers. The tensile modulus of the carbon fiber was 820GPa and the thermal conductivity was 530W / m·K. The surface modification process used 5% ultrasonic-hydrogen peroxide combined oxidation treatment, with an ultrasonic frequency of 25kHz and an ultrasonic power of 1500W. The length of the electrolytic cell and the fiber winding speed were controlled to ensure that the fiber was in the hydrogen peroxide solution for 120s; the electrolyte was 2.5wt% NH 4 HCO 3solution, the current passing through the carbon fiber is fixed at 1A, the fiber winding speed is controlled at 6m / s, and the fiber treatment time in the electrolytic cell is 60s;
[0069] Carbon fiber prepreg is prepared by a two-step process:
[0070] The film production speed was controlled at 6 m / min, and a dispersion containing 10 wt% carbon nanotubes was sprayed on the surface of a 1 m wide film using high pressure at a spray speed of 14 ml / min. The surface density of the carbon nanotubes in the obtained film was 0.22 g / m 2 Specifically, the carbon nanotubes were dispersed in allyl glycidyl ether at a mass ratio of 5 wt%, and dispersed by ultrasonication at a power of 800 W for 2 h, and then the dispersion was placed in a vacuum oven at 80° C. to evaporate to a volume of 1 / 4 of the original volume, thereby obtaining a liquid carbon nanotube dispersion;
[0071] The unwinding speed of the prepreg equipment is controlled to be 2m / min, and a set of guide roller electrodes with adjustable voltage is set in front of the wire comb after unwinding, and the electrode voltage is set to -36V; ultrasonic rod vibration is used on the release paper in front of the cold plate of the prepreg machine, the ultrasonic rod power is 300W, the cold plate is connected to the positive electrode, and the electrode voltage is set to 12V.
[0072] After rolling, a carbon fiber prepreg with carbon nanotubes vertically rooted on the surface is obtained.
[0073] Then the prepreg is hot pressed. The hot pressing is carried out in an autoclave, with tempered glass on the bottom and stainless steel plate on the top as the hot pressing mold. When the mold is in use, it is necessary to clean the mold with a mold cleaning agent, apply the release agent 3 to 5 times, wipe it with a dry cloth after applying the release agent, and then apply the release agent; after all the coating is completed, let it stand for 5 to 10 minutes.
[0074] During hot pressing, three layers of carbon fiber prepreg are laid orthogonally on a smooth tempered glass mold. The first and third layers are polyacrylonitrile-based carbon fiber layers, and the prepreg surface density is 30g / m 2 , fiber surface density is 21g / m 2 , thickness is 30μm; the second layer is a high-performance asphalt-based carbon fiber layer, and the prepreg surface density is 140g / m 2 , fiber surface density is 100g / m 2 , thickness is 80μm;
[0075] A stainless steel plate is used as a hot pressing mold on the upper side of the prepreg to ensure that the temperature of the upper prepreg is slightly higher than that of the lower side to facilitate the discharge of pores, and to ensure that the upper and lower prepregs have different shrinkage rates after cooling to facilitate demoulding; after the ply is completed, it is vacuum treated with a vacuum negative pressure of -0.12MPa. The autoclave uses air as the medium with an air pressure of 0.6MPa;
[0076] Use two steps of heating to carry out the chain extension, cross-linking and curing reactions of the epoxy system, that is, first heat up to 90°C, keep warm for 30 minutes, then heat up to 130 degrees Celsius, keep warm for 2 hours, and then cool to below 60°C before taking out the rough carbon fiber screen support structure. Then the rough carbon fiber screen support structure is processed. The processing is carried out by electric spark wire cutting. The power supply voltage is 80V, the servo reference voltage is 12V, the peak current is 6.4A, the electrode wire is negative polarity, the pulse width interval is 20μs, the pulse width is 0.3μs, the inter-electrode medium is deionized water, and the servo feed speed is 2mm / min. After machining is completed, the support layer is coated to obtain the carbon fiber screen support structure product for the folding screen;
[0077] The overall thickness of the carbon fiber screen support structure is 0.120±0.005 mm, the in-plane thermal conductivity is 87.6 W / m·K, the out-of-plane thermal conductivity is 5.1 W / m·K, and the asphalt-based carbon fiber directional tensile modulus is 248 GPa.
[0078] Example 2
[0079] This embodiment provides a high thermal conductivity carbon fiber screen support layer, and the preparation method of the high thermal conductivity carbon fiber screen support layer includes the following steps:
[0080] Only asphalt-based carbon fibers are treated. Specifically, after the continuous carbon fiber is unrolled, it is graphitized at 2600°C, and then surface modified, electrolyzed, washed, dried, sizing, dried and wound to obtain two continuous amino-functionalized carbon fibers. The tensile modulus of the carbon fiber is 750GPa and the thermal conductivity is 480W / m·K. The surface modification process uses 5% ultrasonic-hydrogen peroxide combined oxidation treatment, with an ultrasonic frequency of 25kHz and an ultrasonic power of 1500W. The length of the electrolytic cell and the fiber winding speed are controlled to ensure that the fiber is in the hydrogen peroxide solution for 120s; the electrolyte is 2.5wt% NH 4 HCO 3 solution, the current passing through the carbon fiber is fixed at 1A, the fiber winding speed is controlled at 6m / s, and the fiber treatment time in the electrolytic cell is 60s;
[0081] Carbon fiber prepreg is prepared by a two-step process:
[0082] The film production speed was controlled at 6 m / min, and a dispersion containing 10 wt% carbon nanotubes was sprayed on the surface of a 1 m wide film using high pressure at a spray speed of 14 ml / min. The surface density of the carbon nanotubes in the obtained film was 0.07 g / m 2Specifically, the carbon nanotubes were dispersed in allyl glycidyl ether at a mass ratio of 5 wt%, and dispersed by ultrasonication at a power of 1500 W for 2 h, and then the dispersion was placed in a vacuum oven at 80° C. to evaporate to a volume of 1 / 4 of the original volume, thereby obtaining a liquid carbon nanotube dispersion;
[0083] The unwinding speed of the prepreg equipment is controlled to be 2m / min, and a set of guide roller electrodes with adjustable voltage is set in front of the wire comb after unwinding, and the electrode voltage is set to -24V; ultrasonic rod vibration is used on the release paper in front of the cold plate of the prepreg machine, the ultrasonic rod power is 300W, the cold plate is connected to the positive electrode, and the electrode voltage is set to 12V.
[0084] After rolling, a carbon fiber prepreg with carbon nanotubes vertically rooted on the surface is obtained.
[0085] Then the prepreg is hot pressed. The hot pressing is carried out in an autoclave, with tempered glass on the bottom and stainless steel plate on the top as the hot pressing mold. When the mold is in use, it is necessary to clean the mold with a mold cleaning agent, apply the release agent 3 to 5 times, wipe it with a dry cloth after applying the release agent, and then apply the release agent; after all the coating is completed, let it stand for 5 to 10 minutes.
[0086] During hot pressing, the surface density of the first layer of prepreg is 30g / m 2 , fiber surface density is 21g / m 2 , thickness is 30μm; the second layer is a high-performance asphalt-based carbon fiber layer, and the prepreg surface density is 100g / m 2 , fiber surface density is 70g / m 2 , with a thickness of 60μm; a stainless steel plate is used as a hot pressing mold on the upper side of the prepreg to ensure that the temperature of the upper prepreg is slightly higher than that of the lower side to facilitate the discharge of pores, and at the same time ensure that the different shrinkage rates of the upper and lower measurements after cooling are convenient for demoulding; after the ply is completed, it is vacuum treated with a vacuum negative pressure of -0.12MPa, and the autoclave uses air as the medium with an air pressure of 0.6MPa;
[0087] Use two steps of heating to carry out the chain extension, cross-linking and curing reactions of the epoxy system, that is, first heat up to 90°C, keep warm for 30 minutes, then heat up to 130 degrees Celsius, keep warm for 2 hours, and then cool to below 60°C before taking out the rough carbon fiber screen support structure. Then the rough carbon fiber screen support structure is processed. The processing is carried out by electric spark wire cutting. The power supply voltage is 80V, the servo reference voltage is 12V, the peak current is 6.4A, the electrode wire is negative polarity, the pulse width interval is 20μs, the pulse width is 0.3μs, the inter-electrode medium is deionized water, and the servo feed speed is 2mm / min. After machining is completed, the support layer is coated to obtain the carbon fiber screen support structure product for the folding screen;
[0088] The overall thickness of the carbon fiber screen support structure is 0.120±0.005 mm, the in-plane thermal conductivity is 78.3 W / m·K, the out-of-plane thermal conductivity is 4.7 W / m·K, and the asphalt-based carbon fiber directional tensile modulus is 212 GPa.
[0089] In summary, the carbon fiber support plate provided by the present invention has high rigidity, can be light and thin while achieving better supporting effect; the carbon fiber support plate provided by the present invention has good electrical conductivity, and can meet the processing requirements of high-precision wire cutting technology; the carbon fiber support plate provided by the present invention has the characteristics of high in-plane and interlayer thermal conductivity, which meets the higher heat dissipation requirements of smart phones.
[0090] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber screen support structure, characterized in that: The steps include: S1: After graphitizing continuous PAN-based carbon fibers and continuous asphalt-based carbon fibers, oxidizing the PAN-based carbon fibers and the asphalt-based carbon fibers, electrolyzing, washing, drying, sizing, and baking, surface-modified PAN-based carbon fibers and surface-modified asphalt-based carbon fibers are obtained; S2: impregnating the surface-modified PAN-based carbon fiber and the surface-modified asphalt-based carbon fiber on the surface of the epoxy resin film loaded with amino carbon nanotubes, and connecting the surface-modified PAN-based carbon fiber and the surface-modified asphalt-based carbon fiber to an electric field during the impregnation process, so that the carbon nanotubes are vertically rooted on the surface of the carbon fiber to obtain the surface-modified PAN-based carbon fiber prepreg and the surface-modified asphalt-based carbon fiber prepreg; S3 alternately orthogonally lay two layers of surface-modified PAN-based carbon fiber prepreg and one layer of surface-modified asphalt-based carbon fiber prepreg, so that a layer of surface-modified asphalt-based carbon fiber prepreg is sandwiched between the two layers of surface-modified PAN-based carbon fiber prepreg, and then orthogonally lay and hot-press to obtain a rough blank of a carbon fiber support structure; or Three layers of surface-modified asphalt-based carbon fiber prepreg are continuously orthogonally laid and then hot-pressed to obtain a rough blank of a carbon fiber support structure; finally, the rough blank is subjected to electric spark wire cutting to obtain a carbon fiber screen support structure.
2. The method for preparing a carbon fiber screen support structure according to claim 1, characterized in that step: The oxidation comprises the steps of ultrasonic wave-hydrogen peroxide combined oxidation treatment; The concentration of hydrogen peroxide used in the ultrasonic-hydrogen peroxide combined oxidation treatment is 5wt%; The ultrasonic-hydrogen peroxide combined oxidation treatment adopts an ultrasonic frequency of 20-25kHz; The ultrasonic power used in the ultrasonic-hydrogen peroxide combined oxidation treatment is 800-1500W; The ultrasonic wave-hydrogen peroxide combined oxidation treatment is carried out for 100-120 seconds.
3. The method for preparing the carbon fiber screen support structure according to claim 1, characterized in that: The electrolyte used in the electrolysis is one of (NH4)3PO4, NH4HCO3, (NH4)2SO4 or NH4H2PO4 solution; The mass fraction used in the electrolysis is 2-2.5wt%; The current used in the electrolysis is 0.5-1.5A; The electrolysis time is 30-60s.
4. The method for preparing a carbon fiber screen support structure according to claim 1, characterized in that : The length of the amino carbon nanotubes is 5 to 15 μm, and the diameter is 8 to 20 nm; The surface density of the carbon nanotubes on the surface of the resin film is 0.07 to 0.22 g / m 2 .
5. The method for preparing a carbon fiber screen support structure according to claim 1, characterized in that : The loading process includes dispersing the amino carbon nanotubes in an active diluent at a mass ratio of 5wt%, dispersing them by ultrasonication for 2h at a power of 800-1000W, and then concentrating them in vacuum at 80°C to a volume of 1 / 4 of the original volume to obtain a carbon nanotube dispersion, and then spraying the liquid carbon nanotube dispersion onto the surface of the epoxy resin film.
6. The method for preparing a carbon fiber branch structure according to claim 5, characterized in that : The active diluent is one of benzyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether and allyl glycidyl ether.
7. The method for preparing a carbon fiber branch structure according to claim 1, characterized in that: The electrification includes the steps of connecting the carbon fiber to a negative electrode of -24 to -36V and connecting the cold plate of the prepreg machine to a positive electrode of 12V.
8. The method for preparing a carbon fiber support structure according to claim 1, characterized in that: When the orthogonal laying is performed, the surface density of the surface-modified PAN-based carbon fiber prepreg is 20 to 30 g / m 2 , fiber surface density is 10g / m 2 ~21g / m 2 , the resin content is 20-40wt%, and the thickness is 12μm-30μm; When orthogonally laid, the surface density of the surface-modified asphalt-based carbon fiber prepreg is 110 to 145 g / m 2 , fiber surface density 75~100g / m 2 , the resin content is 25-30wt%, and the prepreg thickness is 60-80μm; The tensile modulus of the asphalt-based carbon fiber is 700-850 GPa, and the thermal conductivity is 350-550 W / m·K.
9. The method for preparing a carbon fiber branch structure according to claim 1, characterized in that: Also includes the step of machining; The machining includes the steps of using wire electric discharge machining; The power supply voltage used in the EDM wire cutting process is 80V, the servo reference voltage is 8-12V, the servo feed speed is 1.5-2.5mm / min; the peak current is 6.4-8.0A, the pulse width interval is 18-22μs, and the pulse width is 0.15μs-0.3μs; The electrode wire used in the electric spark wire cutting process is a negative polarity electrode wire; The electrode wire and interelectrode medium are deionized water.
10. The method for preparing a carbon fiber screen support structure according to claims 1 to 9, characterized in that: The overall thickness of the carbon fiber screen support structure is 85 μm to 140 μm.
Citation Information
Patent Citations
Carbon fiber supporting structure suitable for folding screen
CN114311872A
Carbon fiber supporting plate as well as preparation method and application thereof
CN114536810A
Flexible folding screen carbon fiber supporting plate
CN217238995U
Cited By
Out-of-plane high-thermal-conductivity carbon fiber composite material and preparation method thereof
CN120481387A
Light and thin carbon fiber supporting layer for flexible folding screen and preparation method of light and thin carbon fiber supporting layer
CN122379067A